ONTOGENESIS AND AGE STRUCTURE OF THE PULSATILLA MULTIFIDA MILL POPULATIONS IN THE CONDITIONS OF NORTHERN KAZAKHSTAN - Sultangazina, G. J.; Kuprijanov А.N.; Kuprijanov О.А.; Beyshov, R.S. (Scientific Journal of Pedagogy and Economics, 2020)
The article provides the study results on the age-related stages of Pulsatilla multifida Mill. The materials have been gathered in the course of field research taking into account the literary data. The studies were carried out in the Pavlodar and Akmola regions during the season of mass flowering and seeds ripening (2018-2019). A rosette shoot is formed on the stage of seedlings out of 3-4 leaves of different complexity. On the juvenile stage the rosette shoot is formed out of 4-5(6) leaves. The leaves are tripartite, dissected into large lobes and in their turn are cut into prongs. The root system is represented by a stem-root and many roots of the second order. Immature individuals undergo the formation of an elongated rhizome. Leaf-blades are tripartite with deeply dissected lobes. 1-3 rosette shoots grow from resumption buds. The calendar age of an immature plant is 1-2 years. On the virginal stage, there is an increase of resumption buds and rosette modules, the formation of a powerful rhizome with numerous resumption buds on it. Leaves acquire a specificity: the number of prongs on the leaves becomes narrow, middle leaves develop a petiole of different lengths. Young generative plants have 1-3 peduncles and 1-3 rosette shoots. On average generative stage, the rhizome forms a many-headed caudex with numerous rosette shoots. In old age the number of rosette shoots decreases, the peduncles remain underdeveloped and do not start blooming. The leaves are cut into very narrow lobes with a large number of prongs, while the length of the petiole at the central lobe becomes minimal. In subsenile plants, there is a maceration of rhizomes to a greater depth with the formation of vegetative rosettes on separate parcels and they are represented by a system of dying rhizomes, with single vegetative sockets. The coenopopulations of P. multifida and P. aggr. patens are found in rocky habitats, except CP-1 (a glade between the rocks) where P. multifida grows on a dry meadow among steppe shrubs. All the studied populations are generative, the density of species is high enough to ensure the normal existence of the species in natural conditions.